2017
DOI: 10.1016/j.aott.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Is pin configuration the only factor causing loss of reduction in the management of pediatric type III supracondylar fractures?

Abstract: ObjectiveClosed reduction with percutaneous pinning is the treatment of choice for displaced supracondylar humerus fractures in children. In addition to configuration of pin fixation, many factors have been attributed to loss of reduction (LOR). The aim of the present study was to review potential factors that contribute to loss of reduction in the closed management of type III pediatric supracondylar fractures.MethodsTreatment of 87 patients with type III supracondylar fractures was reviewed to determine fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
4
27
0
3
Order By: Relevance
“…Pin configuration and pin spread along the fracture line among other factors have been said to be associated with loss of reduction in the management of SHFs [2][3][4][5]. To effectively manage distal humerus MDJ fractures, special attention must be paid to the characteristics of the fracture lines.…”
Section: Introductionmentioning
confidence: 99%
“…Pin configuration and pin spread along the fracture line among other factors have been said to be associated with loss of reduction in the management of SHFs [2][3][4][5]. To effectively manage distal humerus MDJ fractures, special attention must be paid to the characteristics of the fracture lines.…”
Section: Introductionmentioning
confidence: 99%
“…It had been reported that proper pin spread at the fracture site could in uence the stability of pins [5]. In our cross pinning con gurations, the best stiffness was achieved when both pins exited around the upper border of the metaphyseal-diaphyseal junction (MDJ).…”
Section: Discussionmentioning
confidence: 79%
“…However, loss of reduction with the technique is a major concern to pediatric orthopedic surgeons. Causes of loss of reduction with pinning techniques have been attributed to pinning con guration, pin size, pin number and pin spread [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 35 patients underwent cross-pinning from lateral/proximal to medial/distal direction. Optimal placement of lateral pins alone with at least 2 mm of divergence at fracture site maybe difficult in proximally located and/or medially comminuted fractures (19,20). Ulnar nerve injury can be a catastrophic complication of pinning of pediatric supracondylar fracture, thus any efforts should be made to avoid it.…”
Section: Discussionmentioning
confidence: 99%